Multiple risk factors for diabetes mellitus in patients with chronic pancreatitis: A multicentre study of 1117 cases. Issue 4 (1st May 2020) - Olesen, Søren S; Poulsen, Jakob L; Novovic, Srdan; Nøjgaard, Camilla; Kalaitzakis, Evangelos; Jensen, Nanna M; Engjom, Trond; Tjora, Erling; Waage, Anne; Hauge, Truls; Haas, Stephan L; Vujasinovic, Miroslav; et al.
Abstract : Background: Diabetes mellitus is a common complication of chronic pancreatitis. It is traditionally considered to develop as a consequence of beta cell loss, but there might be additional factors. Recent studies have highlighted the importance of type 2 diabetes‐related risk factors in this context and population‐based studies show increased risk of diabetes following acute pancreatitis. The aim of this study was to explore multiple risk factors for diabetes in patients with chronic pancreatitis. Methods: We conducted a multicentre, cross‐sectional study of patients with definitive chronic pancreatitis according to the M‐ANNHEIM criteria. We used multivariable logistic regression models to determine risk factors independently associated with diabetes. Results: The study included 1117 patients of whom 457 (40.9 %) had diabetes. The mean age was 52.8 ± 14.2 years and 67% were men. On multivariate analysis, parameters indicative of beta cell loss (pancreatic calcification, exocrine insufficiency, pancreatic resection) were confirmed as independent risk factors for diabetes (all p  ≤ 0.02). In addition, type 2 diabetes‐related risk factors (dyslipidaemia and overweight/obesity) were associated with the presence of diabetes (all p  ≤ 0.002). Patients with a history of pancreatic fluid collections (indicative of previous attacks of acute pancreatitis) had a marginally increased risk of diabetes ( p  = 0.07). Conclusion: In patients with chronic pancreatitis the presence of diabetes is associated with multiple risk factors including type 2 diabetes‐related factors. Our observations attest to the understanding of this entity and may have implications for treatment.